1989
DOI: 10.1111/j.1365-2125.1989.tb03524.x
|View full text |Cite
|
Sign up to set email alerts
|

A dose rising study of the safety and effects on serum prolactin of SK&F 101468, a novel dopamine D2‐receptor agonist.

Abstract: 1. SK&F 101468, a non phenolic indolone derivative, has been characterised preclinically as a novel, potent and specific dopamine D2‐ receptor agonist. 2. Its tolerability and effects on serum prolactin were investigated in 14 healthy male volunteers in a study of the first administration of SK&F 101468 to man. 3. Doses between 80 micrograms and 2.5 mg caused statistically significant (P less than 0.05) lowering of basal and food stimulated serum prolactin, relative to placebo, over a 6 h post treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
3
13
0
Order By: Relevance
“…The single-dose pharmacokinetics of ropinirole in this hyperprolactinaemic cohort were similar to those described earlier in healthy volunteers [11]. Systemic exposure to ropinirole seems to increase with dose as does the transient decrease in prolactin concentrations.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The single-dose pharmacokinetics of ropinirole in this hyperprolactinaemic cohort were similar to those described earlier in healthy volunteers [11]. Systemic exposure to ropinirole seems to increase with dose as does the transient decrease in prolactin concentrations.…”
Section: Discussionsupporting
confidence: 84%
“…The effect of a single dose of ropinirole on prolactin concentrations was previously evaluated in 14 healthy subjects, at doses ranging from 0.8 to 2.5 mg. In these subjects, ropinirole lowered serum prolactin concentrations relative to placebo and a single 2.5 mg ropinirole dose decreased mean serum prolactin concentrations by 42% . Due to the rarity of prolactinomas, which have a prevalence of only 100 cases per million in the general population, large clinical studies in this population can be difficult to conduct.…”
Section: Discussionmentioning
confidence: 98%
“…By comparison the mean maximum increase in prolactin following 400 mg of sulpiride was significantly higher than that produced by 10 mg DU 29894. The increase produced by 3 mg haloperidol was significantly less than that following 10 ported to the pituitary lactotrophs by the pituitary lime (h) portal system and inhibits prolactin release [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Ropinirole, SK&F 101468, (4-[2-dipropylamino)ethyl]-1,3-dihydro-2H-indol-2-one, monochloride), is a novel non-phenolic indolone derivative which acts as a dopamine D2-receptor agonist (Gallagher et al, 1985). Previous studies in healthy subjects showed that single doses of ropinirole could cause nausea, orthostatic hypotension and prolactin inhibition (Acton & Broom, 1989;de Mey et al, 1990). Domperidone is a well established dopamine D2receptor antagonist practically devoid of central effects (Heykants et al, 1981;Kohli et al, 1983;Laduron & Leysen, 1979;Niemegeers et al, 1980).…”
Section: Introduction Methodsmentioning
confidence: 99%